Learning Trajectory of Whole Numbers using the Context of Muara Enim Melemang Based on Realistic Mathematics Education (PMRI) - Arbella Sri Marleny M.; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Yusuf Hartono (Universitas Muhammadiyah Mataram, 2026)
Learning whole numbers in the early grades of elementary school often poses challenges because students must understand abstract concepts and represent them symbolically. This study focuses on developing a Local Instructional Theory (LIT) for learning whole numbers using the Muara Enim melemang cultural context within the Pendidikan Matematika Realistik Indonesia (PMRI) framework. The research contributes both to the development of learning theory (LIT) and to improving the effectiveness of culturally based mathematics learning in Indonesian primary schools. The study employed design research (validation study) consisting of three stages: (1) the preliminary design formulated a Hypothetical Learning Trajectory (HLT) through curriculum analysis and contextual task design; (2) the teaching experiment tested the HLT in classroom practice to explore students’ strategies and interactions; and (3) the retrospective analysis compared the HLT and the Actual Learning Trajectory (ALT) to refine the emerging instructional theory. Findings reveal that the predicted HLT aligned with the ALT. Students successfully developed number sense counting, comparing, ordering, and performing simple operations through concrete representations of lemang. Difficulties mainly appeared in symbolic notation, such as using inequality signs and subtraction symbols. The study’s novelty lies in establishing a local culture-based LIT that bridges PMRI principles with ethnomathematics. Practically, it provides a contextual model teachers can adopt to enhance meaningful mathematics learning in early grades.